2017
DOI: 10.1177/1098612x17699477
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of more than 9000 feline cutaneous tumours in the UK: 2006–2013

Abstract: Objectives The aim of the study was to utilise a large database available from a UK-based, commercial veterinary diagnostic laboratory to ascertain the prevalence of different forms of cutaneous neoplasia within the feline population, and to detect any breed, sex or age predilections for the more common tumours. Methods Records from the laboratory were searched for feline submissions received between 31 May 2006 and 31 October 2013. For masses arising within the skin for which histopathology had been performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 8 publications
7
45
0
1
Order By: Relevance
“…1,5,11,12 SCC was the main tumour histotype diagnosed in this study, while it was only the second most common in an earlier UK-based study, and the third most common in American, Swiss and South African studies, as well as in the most recent UK-based study, the last reporting only skin-related tumours. 1,2,4,5,13 Moreover, in our study this tumour type was also the most common feline cancer observed in the oral cavity (46%), usually affecting older cats, and with 54.5% of cases originating from gingival mucosa. According to the recent literature, 10% of all tumours diagnosed in cats are oral tumours and SCC is the most common; gingiva, the sublingual area and tongue were reported as the most commonly affected sites.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…1,5,11,12 SCC was the main tumour histotype diagnosed in this study, while it was only the second most common in an earlier UK-based study, and the third most common in American, Swiss and South African studies, as well as in the most recent UK-based study, the last reporting only skin-related tumours. 1,2,4,5,13 Moreover, in our study this tumour type was also the most common feline cancer observed in the oral cavity (46%), usually affecting older cats, and with 54.5% of cases originating from gingival mucosa. According to the recent literature, 10% of all tumours diagnosed in cats are oral tumours and SCC is the most common; gingiva, the sublingual area and tongue were reported as the most commonly affected sites.…”
Section: Discussionmentioning
confidence: 46%
“…Cancer is a frequent disease in domestic cats and yet few major studies are published regarding the occurrence of tumours in the feline population in different countries, including both the USA and Europe. [1][2][3][4][5] These studies vary with respect to data source, sample numbers, size of the assessed geographical region and availability of population data (epidemiologic denominator). Cat breeds are dispersed around the world; thus, feline medicine clinicians should be aware of the breeds more commonly encountered in their regions.…”
Section: Introductionmentioning
confidence: 99%
“…. In our report feline lipoma reports were almost double that of an earlier study, 7 warranting further investigation. Table 2 shows the proportions of common dog breeds attending veterinary practices, as recorded by SAVSNET between 2018 and 2019, with the percentage of such breeds afected by the ive most commonly reported skin tumours identiied in this newly formed tumour registry.…”
Section: Treatment and Controlsupporting
confidence: 58%
“…The total number of feline submissions to the laboratory from 31 May 2006 to 31 October 2013 was 219,083, including blood samples, cytology and histopathology submissions. 12 Of these, samples arising from the nasal cavity comprised 0.18% (n = 405).…”
Section: Resultsmentioning
confidence: 99%